Processing L2 action verbs shares the same mechanisms for processing L1 items: evidence from a combined behavioral and MEG study - Visani, Elisa; Rossi Sebastiano, Davide; Garofalo, Gioacchino; Duran, Dunja; Tangorra, Melania; Mezzadri, Marco; Buccino, Giovanni (Frontiers in Psychology, 2025)
IntroductionExperimental evidence shows that the sensorimotor system is not only involved in performing actions but also in observing and understanding them, even when verbally described. The involvement of the sensorimotor system in processing action related language material is known as embodiment. Following this approach, language items presented in L1 and L2 should affect motor activity in the same manner.MethodsThis study aimed to investigate the involvement of motor system during the processing of L2 items in a combined behavioral and MEG study. Healthy Italian native speakers performed a semantic decision task on hand and foot actions presented by means of pictures or verbs expressed in English as L2.ResultsResults showed slower hand reaction times and weaker suppression of Beta band power during the processing of hand-related pictures and verbs, as compared to foot-related pictures and verbs, thus suggesting shared neural mechanisms for semantic processing of visually and verbally presented items.DiscussionThis in line with a similar study where Italian verbs were used as language items. However, while no dissimilarity was found in the modulation of the motor system during the processing of verbs presented in L1 and pictures depicting actions in the same category, here, when processing L2 verbs, reaction times were slower than when processing visually presented actions, thus implying an additional cost for processing L2 as compared to L1 verbal items.ConclusionWe argue that these findings support embodiment, in that they can be explained by a similar, although stronger involvement of the sensorimotor system during the processing of L2 verbal items.